Prevalence of psychiatric disorders and associated risk factors in women during their postpartum period: a major public health problem and global comparison - Bener A; Gerber LM; Sheikh J (Dove Medical Press, 2012)
Abdulbari Bener1–3, Linda M Gerber3, Javaid Sheikh41Department of Medical Statistics and Epidemiology, Hamad Medical Corporation, Hamad General Hospital, Qatar; 2Department of Evidence for Population Health Unit, School of Epidemiology and Health Sciences, University of Manchester, Manchester, United Kingdom; 3Department of Public Health, 4Department of Psychiatry, Weill Cornell Medical College, QatarBackground: Postnatal depression has received considerable research and clinical attention; however, anxiety and stress in postpartum women have been relatively neglected.Objective: The aim of this study was to determine the prevalence of depression, anxiety, and stress during the postpartum period of women using the Depression Anxiety Stress Scales, and to examine the associated correlates of these conditions.Design: This was a cross-sectional study conducted from January 2010 to May 2011.Setting: Primary health care centers of the State of Qatar Supreme Council of Health.Subjects: A representative sample of 2091 women who attended primary health care centers was surveyed. From this sample, 1659 women (79.3%) consented to participate in the study.Methods: The study was based on a face-to-face interview using a designed questionnaire covering sociodemographic characteristics, family history, medical history, the obstetric variables of patients, and stressful life events. Depression, anxiety, and stress were measured using the Depression Anxiety Stress Scales.Results: In the study sample, the prevalence of depression, anxiety, and stress was 18.6%, 13.1%, and 8.7%, respectively. Young mothers and those with higher education (above secondary level) were more depressed (35.7% and 67.5%, respectively), anxious (34.9% and 68.3%, respectively), and under stress (29.7% and 62.1%, respectively) in their postpartum period. Postpartum working women were more stressed (60.7%) and anxious (51.8%), while housewives were more depressed (51.6%). Nearly half of the depressed mothers reported experiencing more than one stressful life event in their postpartum period, such as low income (41.9%; P = 0.05) or unplanned pregnancy (60.4%; P < 0.001). Unplanned pregnancy (OR = 1.9; P < 0.001) was the major significant correlate for postpartum depression, while a lack of family support (OR = 1.9; P < 0.001) was the major significant correlate for postpartum anxiety. For stress, being an older mother aged from 40 to 45 years of age (OR = 2.0; P = 0.04) and having dissatisfaction in married life (OR = 1.9; P = 0.006) were the significant correlates.Conclusion: The study found clearly defined groups of women at risk for postpartum depression, anxiety, and stress. There was a marked association between stressful life events and postpartum depression, anxiety, and stress disorders.Keywords: prevalence, obstetric risks, Qatar, depression, postpartum